DNA-inspired, highly packed supercoil battery for ultra-high stretchability and capacity. (July 2021) - Lee, Jae Myeong; Chun, Sungwoo; Son, Wonkyeong; Suh, Dongseok; Kim, Shi Hyeong; Kim, Hyun; Lee, Dongyun; Kim, Younghoon; Kim, Young-Kwan; Lim, Sang Kyoo; Choi, Changsoon
Abstract: Stretchable yarn/fiber energy storage devices with a high energy density are highly beneficial for use in wearable applications. Although some studies on stretchable fiber batteries have been conducted, the development of fiber batteries that combine outstanding stretchability with a high energy storage capacity has been restricted by the tradeoff between stretchability and the active material content. In the present study, a DNA-inspired supercoil battery is proposed and fabricated via the secondary twisting (i.e. supercoiling) of a fiber electrode consisting of an elastomeric core fiber and a conductive sheath containing nano-sized active materials. The structural changes induced by supercoiling facilitate the effective packing of the electrode into coil and supercoil loops that represent only 29% of the initial length. The resulting highly packed supercoil battery exhibits an outstanding stretchability (800%) and linear capacity (0.029 mAh/cm) compared to non-coil, coil, and previously reported stretchable yarn/fiber-based batteries. Graphical Abstract: DNA-inspired supercoil electrode is realized by the over-twisting of fiber electrode. The resulting supercoil Zn/MnO2 battery achieves both high elasticity of 800% and high energy storage performance of 0.029 mAh/cm. ga1 Highlights: DNA-inspired supercoil battery is realized by the over-twisting of fiber. Supercoiling facilitates the compact packing of the fiber into supercoil loops so that 29% of the initial length remains. The resulting Zn/MnO2 supercoil battery achieves both high elasticity of 800% and energy capacity of 0.029 mAh/cm. This stretchable battery provides the potential of energy source for wearable, miniature or implantable devices.